Gambaran Pengetahuan Ibu Bersalin Tentang Ketuban Pecah Dini di RSIA Artha Mahinrus Medan Tahun 2022 - Ika Damayanti Sipayung; Ridesman Ridesman; Riska Susanti Pasaribu; Lasria Yolivia Aruan; Esra S.M Tambunan (Pusat riset dan Inovasi Nasional, 2022)
The aim of the study was to find out the description of the knowledge of mothers about premature rupture of membranes at RSIA Artha Mahinrus Medan in 2022.Background: One of the causes of high maternal morbidity and mortality is caused by premature rupture of membranes. Premature rupture of membranes is the rupture of the membranes before there are signs of labor and wait one hour before the start of labor. The incidence of premature rupture of membranes is close to 10% of all deliveries (Manuaba, 2013). Purpose: This study aims to describe or describe the knowledge of mothers about premature rupture of membranes. Methods: The type of research used was descriptive with a cross-sectional approach, the population in the study There were 87 mothers giving birth with a sample of 53 respondents. The sample technique used was accidental sampling, the analysis used was univariate analysis. Results: The study concluded that the high knowledge of birth mothers is strongly influenced by education and experience. Where from 68 respondents with higher education who have good knowledge as many as 18 respondents (72.0%). Experienced birth mothers who had good knowledge were 23 respondents (60.5%). Conclusion: Knowledge of mothers about premature rupture of membranes during pregnancy is greatly supported by education and experience. Therefore it is suggested that all parties improve services, especially in providing information about the importance of preventing premature rupture of membranes.